2016
DOI: 10.1111/eos.12249
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human bone morphogenetic protein‐9 potently induces osteogenic differentiation of human periodontal ligament fibroblasts

Abstract: To accomplish effective periodontal regeneration for periodontal defects, several regenerative methods using growth and differentiation factors, including bone morphogenetic proteins (BMPs), have been developed. Bone morphogenetic protein-9 exhibits the most potent osteogenic activity of this growth factor family. However, it is unclear whether exogenous BMP-9 can induce osteogenic differentiation in human periodontal ligament (PDL) fibroblasts. Here, we examined the effects of recombinant human (rh) BMP-9 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Therefore, other BMP family‐member proteins including BMP9 have especially been shown to play an important role in osteogenesis. rhBMP9 demonstrated more osteopromotive potential via different signaling cascades from rhBMP2 based on several in vitro studies …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other BMP family‐member proteins including BMP9 have especially been shown to play an important role in osteogenesis. rhBMP9 demonstrated more osteopromotive potential via different signaling cascades from rhBMP2 based on several in vitro studies …”
Section: Discussionmentioning
confidence: 99%
“…BMP9, an autocrine/paracrine cytokine in the liver, has been confirmed to be one of the most osteoinductive BMPs for inducing osteoblastic differentiation of MSCs both in vitro and in vivo using adenovirus‐transfection or recombinant human BMP9 methods [Kang et al, ; Fujioka‐Kobayashi et al, ; Li et al, ]. As reported, rhBMP9 increased expressions of Osterix, BSP, and OPN in hPDL fibroblasts compared with that stimulated by rhBMP2 [Fuchigami et al, ]. Several studies also demonstrate BMP9 has an effect on inducing spinal fusion and fracture non‐union repair in animal models [Dumont et al, ; Kimelman‐Bleich et al, ].…”
Section: Discussionmentioning
confidence: 97%
“…In a series of in vitro experiments, it was found that rhBMP9 demonstrated much higher expression of ALP and alizarin red staining on osteoprogenitor cells and periodontal ligament cells when compared to rhBMP2. [13][14][15] Moreover, 2 animal studies in rats demonstrated that rhBMP9 loaded on either an absorbable collagen or chitosan sponge significantly promoted new bone formation when compared to negative control samples. 16,17 While it is know that rhBMP9 has superior osteoinductive potential when compared to rhBMP2, the selection of a suitable carrier material is essential for its delivery, retention and release profile over time.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, rhBMP9 has recently been made commercially available and compared to rhBMP2 for its regenerative potential. In a series of in vitro experiments, it was found that rhBMP9 demonstrated much higher expression of ALP and alizarin red staining on osteoprogenitor cells and periodontal ligament cells when compared to rhBMP2 . Moreover, 2 animal studies in rats demonstrated that rhBMP9 loaded on either an absorbable collagen or chitosan sponge significantly promoted new bone formation when compared to negative control samples .…”
Section: Introductionmentioning
confidence: 99%